RELATIONS BETWEEN FEMALE REPRESENTATION IN PUBLIC AND PRIVATE SPACES BY MARIA BENEDITA BORMANN - Souza, Aldinida de Medeiros (Revista Ártemis, 2013)
Maria Benedita Câmara Bormann is an authoress of the nineteenth century that has been much studied recently, since the attention given to their works, by Gender Studies. Our study takes as the object for analysis the novel Celeste (1988). The goal in this work consists of analyzing the space of the house and its relationship with such characters, especially the protagonist with Celeste, because we can see the author in writing a critique of social relations of the period to which makes reference the novel. The importance of space highlights the events connected with the main character, considering that his life goes through many changes, and with it also change spaces frequented, whether public or private environments.